Effect of twist level on the mechanical performance of S-glass yarns and non-crimp cross-ply composites. Issue 2 (June 2022) - Dalfi, Hussein Kommur; Tausif, Muhammad; yousaf, Zeshan
High modulus/high strength continuous fibres are used extensively for manufacturing textile preforms, as a reinforcement, for composites due to their excellent specific properties. However, their brittle behaviour and tendency to separate easily into individual filaments or bundles can lead to damages during manufacturing processes such as weaving and braiding. Thus, the critical step in the development of an optimal yarn for textile-reinforced composites is to find an optimum twist, which results in a minimum loss of properties of the composite laminates, while maintaining good processability and sufficient strength for textile and/or composite manufacturing. In this study, twist level has been varied to improve the handling and tensile properties of S-glass yarns (i.e. tensile strength). Varying levels of yarn twist (15–40 twists metre −1 ) were employed to study its impact on the tensile properties (i.e. tensile strength, modulus, elongation at break etc.). Furthermore, the effect of twist on the tensile properties of non-crimp cross-ply composites produced via vacuum infusion process was studied. It was observed that mechanical performance (i.e. tensile strength properties) of twisted yarns is improved up to 30 twists metre −1 while it is deteriorated at 40 twists metre −1 . At yarn level, the experimental results were compared with theoretical estimations utilizing existing models for twisted yarns properties. Discrepancies were observed between experimental and theoretical results especially for high level of twist. The tensile strength and elongation of S-glass cross-ply composites at all levels of twist were higher compared to the composite laminates manufactured by using non-twisted yarns. At composite level, the experimental results were also computed employing rule of mixture and good agreement was observed between experimental and predicted results.